Elephant translocations - A. Coetsee (Pachyderm)
Only the summary of the presentation, which was accompanied by a video taped film, was published. Reviews the 1993 removal of 670 elephants in family units from Gonarezhou National Park - 470 to large conservation areas in Zimbabwe and 200 to Madikwe Reserve in South Africa. The exercise proved elephant herds can be successfully captured and translocated over long distances thus providing an option to culling when alternative land areas are available.